Isolation and mapping of novel mouse brain cDNA clones containing trinucleotide repeats, and demonstration of novel alleles in recombinant inbred strains. - Chambers, D M; Abbott, C M

(untitled) (Genome Research, 1996)
Abnormal expansion of trinucleotide repeats (TRs) has now been implicated in the pathogenesis of at least nine human genetic disorders, particularly those in which anticipation and/or fragile sites have been demonstrated. Anticipation, the phenomenon of increasing severity of phenotype in successive generations, has never been seen in species other than man. Nevertheless, animal models for the dynamic mutation of TRs would be extremely valuable. We have screened a mouse brain cDNA library in an attempt to identify clones representing each of the 10 possible classes of trinucleotide repeat. Thirty-seven clones were analyzed in detail. Of the 37 sequences, 18 displayed significant levels of homology with sequences in GenBank, 10 of them with human expressed sequence tags (ESTs). We then analyzed 25 of the clones by PCR of the sequence containing the repeat in a number of different mouse strains and species to assess levels of variability of repeat length. Of the 25 clones analyzed in this way, 64% showed length variation between Mus musculus spp. and Mus spretus, and 32% showed variation between Mus musculus musculus-derived standard laboratory inbred strains. Where variation was detected (17 repeat-containing clones in all), the gene was mapped by linkage analysis. None of the repeats isolated showed any signs of extreme expansion. However, two of the repeats were shown to have undergone size changes during the establishment of a number of recombinant inbred strains, suggesting that these repeats are at least moderately unstable.